The Use and Abuse of Ptolemy’s Tetrabiblos in Renaissance and Early Modern Europe: Two Case Studies (Giovanni Pico della Mirandola and Filippo Fantoni) - Rutkin, H. Darrel (Ptolemy in Perspective, 2010)
Not so very long ago, astrology was taught within the scientific curriculum of the finest European universities, especially in Italy, where it was taught from at least the beginning of the fourteenth through the middle of the seventeenth centuries. According to the University of Bologna’s 1405 statutes, which articulate the basic structures of arts education in the premodern Italian universities, astrology was primarily taught in the four-year mathematics course, although it was also taught in different respects in the natural philosophy and medical courses. After prerequisites in arithmetic, geometry and elementary mathematical astronomy, the students began their study of astrology proper in the third year; in the fourth, they advanced to the higher levels of scientific astronomy and astrology by reading two of Ptolemy’s fundamental texts, the Almagest and Tetrabiblos.1
Created from Fastlane, Scopus look-up
Keywords: Celestial Body; Disciplinary Structure; Heavenly Body; Latin Translation; Seventeenth Century